Analisis PDB Dan Inflasi Terhadap Investasi Industri Kimia, Farmasi Dan Obat Tradisional Periode 2017-2022 - Indrawati, Budi; Natasia Rahajeng, Vika; Duvadilan Wibowo, Viko; Noprizon (BULLET : Jurnal Multidisiplin Ilmu, 2024)
The impact of the Covid-19 pandemic in 2020 caused the non-oil and gas industrial sector in Indonesia to experience a decline. This decline was caused by hampered growth in most industrial groups. Of the fifteen existing industry groups, eleven experienced contraction, while only four groups recorded positive growth. Among the four groups that grew, two of them experienced a significant decline in growth, while the other two groups experienced an increase, namely the Chemical, Pharmaceutical and Traditional Medicine Industries and the Basic Metal Industry. This research aims to determine the influence of macroeconomic variables, namely Gross Domestic Product (GDP) and Inflation on Investment in the Chemical, Pharmaceutical and Traditional Medicine Industries for the period 2017 - 2022. The research method uses quantitative methods with secondary data from the Central Statistics Agency. 6 year sample for the period 2017 to 2022. Data processing uses the SPSS (Statistical Product for Service Solutions) analysis tool. The research results and conclusions show that partially GDP and inflation have a positive effect on investment in the chemical, pharmaceutical and traditional medicine industries. Simultaneously, GDP and inflation influence investment in the chemical, pharmaceutical and traditional medicine industries for the 2017 - 2022 period.